2002
DOI: 10.1111/j.1365-2621.2002.tb11353.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turkey Meat, Phosphate, Sodium Lactate, Carrageenan, and Konjac on Residual Nitrite in Cured Meats

Abstract: Wieners were chosen as the model system. They were made with mechanically separated turkey meat (MST) and retained more residual nitrite than other such sausages (p Ͻ Ͻ Ͻ Ͻ Ͻ 0.01). Use of sodium tripolyphosphate resulted in a slightly higher residual nitrite in the finished product (p Ͻ Ͻ Ͻ Ͻ Ͻ 0.05). Wieners containing both MST and sodium tripolyphosphate, or either MST or sodium tripolyphosphate showed higher pH values than the control group. A relationship between product pH and residual nitrite level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…Mean pH values for each sample throughout the storage period were as follows: C, 6.13 ± 0.05; HP7, 6.10 ± 0.04; HP20, 6.14 ± 0.04; HP40, 6.20 ± 0.05. No pH changes during the chilled storage of similar meat products have been reported ( , ).…”
Section: Resultsmentioning
confidence: 99%
“…Mean pH values for each sample throughout the storage period were as follows: C, 6.13 ± 0.05; HP7, 6.10 ± 0.04; HP20, 6.14 ± 0.04; HP40, 6.20 ± 0.05. No pH changes during the chilled storage of similar meat products have been reported ( , ).…”
Section: Resultsmentioning
confidence: 99%
“…Honikel ( 2008 ) estimated that the decline in nitrite levels due to heating during manufacturing is about 35% of the added level, and thereafter there is a continuing decrease in nitrite levels during storage. Special features of poultry meat regarding nitrite levels during storage have also been described (Kilic et al 2001 , 2002 ), with a difference between nitrite levels in poultry and pork/beef meat possibly due to pH differences between the products. However, owing to the much higher abundance of haem in red meat compared with chicken, it is also possible that nitrite-induced formation of nitrosylhaem causes greater and faster loss of added nitrite in red meat products (Hammerling et al Forthcoming).…”
Section: Discussionmentioning
confidence: 97%
“…Other important factors are reported as heat processing and storage conditions such as storage time and temperature. It was demonstrated that the amount of residual nitrite decreases in heat‐treated meat products (Kilic et al., 2001, 2002). It has also been stated that the amount of residual nitrite in Chinese sausages decreased with storage (Kuo & Chen, 2004).…”
Section: Resultsmentioning
confidence: 99%